THE EFFECTIVENESS OF SIMKAH IN ENHANCING SERVICES AT THE OFFICE OF RELIGIOUS AFFAIRS IN MANADO CITY - Subeitan, Syahrul Mubarak; Kartoredjo, Ireniza; Sarib, Suprijati; Yusuf, Nasruddin; Bilalu, Naskur (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2024)
The development of information technology presents opportunities for government institutions to enhance the quality of public services, including marriage administration. This study aims to analyze the effectiveness of implementing the Marriage Management Information System (SIMKAH) at the Office of Religious Affairs (KUA) in Wenang District, Manado City, in improving the efficiency, accuracy, and transparency of marriage registration. This research employs a qualitative descriptive method with a normative-empirical approach, where data is collected through direct observation and in-depth interviews with the Head of KUA, marriage registrars, and SIMKAH operators. The findings reveal that SIMKAH facilitates marriage registration and supports data integration with the Civil Registry Office (DUKCAPIL) to verify the identities of prospective brides and grooms, thereby reducing the risk of data manipulation. Additionally, using SIMKAH accelerates data access, enhances transparency, and contributes to better administrative governance in the KUA. Implementing SIMKAH in the Wenang District KUA has significantly improved the quality of marriage registration services, making SIMKAH an efficient and reliable system for supporting digital-based marriage administration.